Macroeconomic Influence on the Evolution of Quality of Banking Loans: The Case of Main Banks in Greece and Poland - Malgorzata BIALAS; Simeon KARAFOLAS (Communications of International Proceedings, 2025)
According to new standards IFRS 9 loans granted by banks are distinguished in three stages: 1 – with good credit quality, 2 – with signs increased risk (but no default) and 3 with default. The paper is interested on the influence of macroeconomic aggregates to the evolution of loans considering the quality of them. The paper examined the financial statements of 4 largest banks operating in Greece and Poland.
Keywords: bank; loans; IFRS 9